Evaluation of Intangible Assets and Best Practices in a Medium-Sized Port Community - Duran-San Martin, C (Elsevier B.V., 2016)
This paper analyses the main factors involved in the knowledge management of different actors participating in a Chilean port community. The intangible assets participating in the creation of value of the port community, which are expressed in ideas, attitudes, perceptions, experiences, information and knowledge management, are evaluated and classified according to community members core competencies. Then, the current situation of public institutions and companies participating in the port community is diagnosed utilizing interviews to experts and relevant actors. The role of the intellectual, structural, and social capital is examined in relation to strategic statements present in the missions of public and private port system companies. The results of the assessment enable to identify the main critical factors in knowledge management, transference, dissemination, collaboration and team work, storage, and best practices. In particular, the Conversation System stage of the Primary Model is analyzed and evaluated, as well as its causes, by actors of the port community and experts. Initiatives fostering collective work and encouraging conversations are proposed. Some of the best practices developed by the port community to create and disseminate stakeholders knowledge are presented. Also, a set of knowledge management indicators and indexes is developed and presented. © 2016 The Author(s).